2005
DOI: 10.1103/revmodphys.77.1321
|View full text |Cite
|
Sign up to set email alerts
|

Odd triplet superconductivity and related phenomena in superconductor-ferromagnet structures

Abstract: We consider novel unusual effects in superconductor-ferromagnet (S/F) structures. In particular we analyze the triplet component (TC) of the condensate generated in those systems.This component is odd in frequency and even in the momentum, which makes it insensitive to non-magnetic impurities. If the exchange field is not homogeneous in the system the triplet component is not destroyed even by a strong exchange field and can penetrate the ferromagnet over long distances. Some other effects considered here and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
1,704
2
20

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,528 publications
(1,754 citation statements)
references
References 201 publications
28
1,704
2
20
Order By: Relevance
“…Although this type of pairing does not occur there, it is possible in certain FSF systems [1,2,13,14] with ordinary singlet pairing in S. This arrangement can induce, via proximity effects, triplet correlations with m = 0 and m = ±1 projections of the total spin. If the magnetization orientations in both F layers are unidirectional and along the quantization axis, symmetry arguments show that only the m = 0 projection along that axis can exist.Odd triplet pairing in F/S structures has been studied in the dirty limit through linearized Usadel-type quasiclassical equations [2,13,14,15]. In this case, it was found that m = 0 triplet pairs always exist.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although this type of pairing does not occur there, it is possible in certain FSF systems [1,2,13,14] with ordinary singlet pairing in S. This arrangement can induce, via proximity effects, triplet correlations with m = 0 and m = ±1 projections of the total spin. If the magnetization orientations in both F layers are unidirectional and along the quantization axis, symmetry arguments show that only the m = 0 projection along that axis can exist.Odd triplet pairing in F/S structures has been studied in the dirty limit through linearized Usadel-type quasiclassical equations [2,13,14,15]. In this case, it was found that m = 0 triplet pairs always exist.…”
mentioning
confidence: 99%
“…The m = ±1 components, for which the exchange field is not pair-breaking, can be long ranged, and were found to exist for nonhomogeneous magnetization. For FSF trilayers [2,16,17], the quasiclassical methods predict that the structure contains a superposition of all three spin triplet projections except when the magnetizations of the F layers are collinear, in which case the m = ±1 components along the magnetization axis vanish. It is noted in Ref.…”
mentioning
confidence: 99%
“…22,23 We also note that the spin-orbitassisted proximity-effect scenario considered here is different from the diffusive ferromagnet case, where the likely mechanism for proximity effect is believed to be the odd-frequency pairing. 23,24 The main argument for the odd-frequency superconductivity is that any anisotropic pairing would decay fast into a disordered metal on a length-scale of order a mean-freepath, while the odd-frequency isotropic pairing is immune from non-magnetic static disorder. This result follows from the Usadel equation if we assume that the non-s-wave part of the disorder-averaged condensate wave-function is small.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58][59] The information available to us is insufficient to determine the nature of proximity-induced superconductivity in the nanowire. As we have mentioned above, odd-frequency s-wave proximity effect, 23,24 studied in the context of diffusive ferromagnets, remains a realistic scenario here. It is well-known that the conversion from singlet to triplet superconductivity within this scenario occurs due to some form of inhomogeneous magnetic moments near the interface.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation